Surgical pre-prosthetic alveoplasty: Bedah pre-prostetik alveoplasti - Eka Pramudita Ramadhany; setiawan; ilma Yudistian (Makassar Dental Journal PDGI Makassar, 2023)
Pre-prosthetic surgery is conducted to restore oral function and facial shape by preparing the oral cavity to receive dental prosthe-sis by redesigning and smoothing sharp or irregular bone edges. This case report presents a 47-year-old male patient who came to RSGM Saraswati with complaints of discomfort with sharp pain in the right maxillary canine region when chewing using a denture that has been used for 4 years. Bone protrusion was cut and irregular ridge was flattened resulted in a better denture sup-porting and comfort when wearing a denture.